Goats and the small farmer dilemma: Problems and potentialities - Sinn, R.; Urquiza, D.; Bossi, A.; Stanton, T.; Wilson, R.T.; Noble, A.L.; Nolan, M.F.; Devendra, C. (Arizona University, 1982)
Describes some of the problems facing goat production in various countries of the world, evaluating the socio-economic importance of goats & their introduction & acceptance among the extremely poor in the cold climate of North Eastern USA, & among small farmers in the Caribbean, Central America, Kenya, Asia & semi arid tropical Africa; with particular reference to project profiles, ownership patterns, social value of goats, the role of women in goat management, available veterinary services & Development possibilities.